2020
DOI: 10.1371/journal.pone.0227824
|View full text |Cite
|
Sign up to set email alerts
|

Modelling zero-truncated overdispersed antenatal health care count data of women in Bangladesh

Abstract: Overdispersion in count data analysis is very common in many practical fields of health sciences. Ignorance of the presence of overdispersion in such data analysis may cause misleading inferences and thus lead to incorrect interpretations of the results. Researchers should account for the consequences of overdispersion and need to select the correct choice of models for the analysis of such data. In this paper, Generalized Linear Models (GLMs) are applied in modelling and analysis of antenatal care (ANC) count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Poisson regression assumes the random component is generalized Poisson distribution [1,[7][8][9][10][11][12].…”
Section: Generalized Poisson Regression Analysis Is Analogous To Poismentioning
confidence: 99%
See 2 more Smart Citations
“…Poisson regression assumes the random component is generalized Poisson distribution [1,[7][8][9][10][11][12].…”
Section: Generalized Poisson Regression Analysis Is Analogous To Poismentioning
confidence: 99%
“…In general, regression analysis has a response variable which is a continuous variable that follows the normal distribution. But there is also a regression analysis that has a response variable not a continuous variable but a discrete variable one of which is Poisson regression analysis [1][2][3][4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…F INDING outliers in data following the Negative Binomial distribution (NBD) is an active research topic, as NBD can be used to model non-negative integer data of various types, such as gene expression counts produced by RNA sequencing (RNA-Seq) [1], medical [2] and social data [3], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Women education was also found to be the significant factor for ensuring adequate ANC visits, antenatal morbidity, and also to reducing child and maternal deaths (Becker, Peters, Gray, Gultiano, and Black 1993;Mohammad et al 2017;Chakraborty, Islam, Chowdhury, Bari, and Akhter 2003;Chowdhury et al 2007). A study on ANC attendance among Bangladeshi women, who started to visit health centre during their pregnancy in order to receive antenatal care, reported that the urban and educated women who belonging to rich family and having access to mass-media were more likely to attend adequate ANC visits compared with their counterparts (Hossain, Akter, Sultana, and Kabir 2020).…”
Section: Introductionmentioning
confidence: 99%